A literatura abolicionista de Maria Firmina dos Reis: o conto “A escrava” - Loureiro Andreta, Bárbara; Peres Alós, Anselmo (Confluenze. Rivista di Studi Iberoamericani, 2016)
The short story “A Escrava”, by the Brazilian author Maria Firmina dos Reis, was published in 1887, a year marked by abolitionist campaigns. The storyis about the suffering experienced by black families that were separated because of the slave traffic among Brazilian provinces during the nineteenth-century. By the suffering lived by the protagonist, we are invited to think about certain problems lived by female slaves, such as the kidnaping of slave’s children, the impediment of maternity, and the violence attached to fertility questions.